2013
DOI: 10.1007/s10519-013-9620-z
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Analysis of Cloned Puppies Derived from an Elite Drug-Detection Dog

Abstract: Since the first cloned dog "Snuppy" was born, many cloned dogs have been produced by somatic cell nuclear transfer (SCNT) technology. We reported the production of seven cloned drug detection dogs (named "Toppies") in 2009. Although their genetic identity was confirmed, similarities in behavior and the drug-detecting ability were not examined. Therefore, this study is the first attempt to examine their behavior. We conducted the Campbell test which is commonly used to evaluate the tendency of dominance. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…In contrast, in the control group all of the drives and the means were inconsistent. Our previous study showed that cloned puppies could be classified into the same group by the Campbell test (Choi et al 2014), and the behaviours of the cloned group were more consistent than those of the control group in this study. While our previous study was conducted with Labrador Retrievers, this study was performed with Beagles.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In contrast, in the control group all of the drives and the means were inconsistent. Our previous study showed that cloned puppies could be classified into the same group by the Campbell test (Choi et al 2014), and the behaviours of the cloned group were more consistent than those of the control group in this study. While our previous study was conducted with Labrador Retrievers, this study was performed with Beagles.…”
Section: Discussionsupporting
confidence: 63%
“…In contrast, other results showed that fear, anxiety and aggression behaviours were not consistent (Stephen and Ledger 2007). The behaviour of cloned dogs has been studied to determine the similarities among animals (Choi et al 2014), and the present study attempted to assess the personality consistency of cloned dogs. This investigation was conducted by comparing cloned and control groups for consistency of their Puppy Aptitude Test (PAT) scores.…”
mentioning
confidence: 86%
“…The canine SCNT technique has been notably improved since Snuppy, the first cloned dog, was born in 2005 (Lee et al., ). This achievement made canine SCNT applicable to various fields such as conservation of endangered species (Choi et al, ; Jang et al, ; Kim et al, ; Oh et al., ), elite working dogs (Choi et al., ; Oh et al., , ) and animal model researches (Hong et al., ; Kim et al., , ).…”
Section: Application Of Canine Scntmentioning
confidence: 99%
“…Through the 10 subtests for puppy aptitude test, they exhibited a similar tendency for the test with the same behaviour type, although these cloned dogs did not show a perfectly identical score for test. Also, in another research, seven cloned detection puppies were analysed for their similarities in behaviour and the ability for drug detection (Choi et al., ). In this study, Campbell test which is generally used to evaluate the dominance tendency was applied for performing behavioural test.…”
Section: Introductionmentioning
confidence: 99%
“…For propagation of dogs with elite abilities, seven cloned drug-sniffing dogs were produced using donor cells from a dog possessing a distinct ability to concentrate and identify specific smells among countless other scents [22]. These cloned dogs displayed similar behavioral patterns, achieved a 100% rate in the selection test for becoming a drug detection dog, and obtained higher scores for the selection test than other naturally bred dogs [7]. However, there is little information available regarding behavioral similarities such as learning, memory and exploratory patterns in cloned dogs.…”
Section: Introductionmentioning
confidence: 99%